Pengembangan Strategi Pemasaran Menggunakan Metode SWOT dan QSPM Terintegrasi Analytic Hierarchy Process - Andika Danang Saputra; Putri Indah Lestari (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This research aims to develop an effective marketing strategy for a company by using SWOT (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix) methods integrated with Analytic Hierarchy Process (AHP). The SWOT method is used to analyze internal and external factors affecting the company, while QSPM helps in evaluating and prioritizing strategies based on the weights and scores obtained from the SWOT analysis. The integration of AHP in this process provides a systematic approach to measuring the relative importance of various factors and strategy alternatives, and ensures more objective and measurable decisions. The results of this study are expected to provide comprehensive and data-driven strategic guidance for the development of more effective marketing strategies, improve the company's competitiveness in the market and achieve better business goals.